Upaya Hukum Kreditur Kendaraan Apabila Perusahaan Pembiayaan Pailit - Zakaria Abbas (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
Financing institutions are a more flexible alternative to banks for meeting the needs of the community, as stipulated in Presidential Regulation No. 9 of 2009. However, financing companies are not immune to the risk of bankruptcy, which can harm vehicle creditors. The main questions that need to be answered are what legal measures creditors can take and what factors cause bankruptcy. This study employs a normative legal method, referencing Law No. 37 of 2004 on Bankruptcy, particularly Articles 11, 13, and 14, which provide creditors with the option to file objections, appeals, or requests for reconsideration. The causes of bankruptcy can also be traced through economic and trade literature. However, the 2004 Bankruptcy Law still has weaknesses, particularly regarding authority in syndicated loans, necessitating clearer regulations to avoid legal confusion, especially in distinguishing the legal status of individual bankrupt debtors from legal entities and their legal consequences.